2012
DOI: 10.5402/2012/247631
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Methylation in Promoters of GSTP1, p16, p14, and RASSF1A Genes in Smokers of North India

Abstract: Promoter hypermethylation plays an important role in the inactivation of tumor suppressor/metabolic genes during tumorigenesis. The screening of high-risk population (smokers) for hypermethylation pattern in tumor suppressor/metabolic genes can be a good noninvasive biomarker tool, which should be included in prognosis so that therapeutic measures can be initiated at an early stage. The purpose of this study was to determine the prevalence of aberrant promoter methylation of GSTP1, p16, p14, and RASSF1A genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…Tobacco smoke contains numerous chemicals that may change the DNA methylation machinery. Tobacco smoke is also known as a source of ROS production, and ROS can lead to change the activity of DNA methyltransferase enzyme, hence changes methylation pattern on a certain gene (Deep et al, 2012). Our result is different from the previous study result.…”
Section: Discussioncontrasting
confidence: 99%
“…Tobacco smoke contains numerous chemicals that may change the DNA methylation machinery. Tobacco smoke is also known as a source of ROS production, and ROS can lead to change the activity of DNA methyltransferase enzyme, hence changes methylation pattern on a certain gene (Deep et al, 2012). Our result is different from the previous study result.…”
Section: Discussioncontrasting
confidence: 99%
“…Tobacco smoking has also been shown to be associated with P16 gene hypermethylation in NSCLC (Zhang et al, 2011). A study of the North Indian population also showed that smoking speeded up the hypermethylation of P16 genes, thus disabling their expression, making the person more susceptible to the risk of lung and other solid carcinomas (Deep et al, 2012). However Tam et al failed to find a relationship between smoking and method of inactivation of P16 gene expression in NSCLC cases (Tam et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, cells expressing less active GST isoforms are more sensible to GST-metabolized toxins compared to cells with balanced GST activity. In a worst case-scenario, cells are incapable to degrade carcinogens or stress-induced toxic intermediates, thus increasing their susceptibility to undergo further steps toward cancer progression or event other diseases ( Deep et al, 2012 ). The GSTP1 ∗ B (Val105) allele is often mentioned within the context of genetic polymorphisms, a GSTP1 variation which is characterized by an A→G sequence transition in codon 105 of exon 5, leading to the exchange of isoleucine by valine, thus decreasing its catalytic activity associated with reduced cell detoxification ability ( Saxena et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%